Environmental instrumentation and analysis handbook - Down, Randy D., ....-; Lehr, Jay H., ....- (Hoboken : Wiley, 2005)
A comprehensive resource for information about different technologies and methods to measure and analyze contamination of air, water, and soil. Serves as a technical reference in the field of environmental science and engineering Includes information on instrumentation used for measurement and control of effluents and emissions from industrial facilities that can directly influence the environment Focuses on applications, making it a practical reference tool
Keywords: Milieuchemie; Milieutechnologie